Competing roles of defects in SrAl2O4:Eu2+, Dy3+ phosphors detected by luminescence techniques. Issue 10 (26th May 2016) - Wang, Y.; Cui, M.; Zhao, Y.; Xia, Z.G.; Finch, A.A.; Townsend, P.D.
Abstract: Abstract : Thermoluminescence (TL) and radioluminescence (RL) spectra of the long-lasting phosphorescence of SrA12 O4 :Eu 2+, Dy 3+ with A1N addition and commercially used SrA12 O4 :Eu 2+, Dy 3+ were compared. Their spectra were slowly recorded over the temperature range from 25 to 673 K (400 °C). A1N offers a higher temperature TL peak, which should lengthen the phosphor lifetime. However, both TL and RL, especially that below room temperature, reveal that there are additional decay paths for the samples of SrA12 O4 :Eu 2+, Dy 3+ with A1N additions. These new defect sites reduce the phosphor efficiency. Some speculative models of potential sites are proposed and discussed. In addition, discontinuous intensity changes have been observed for both sample types in TL and RL spectra, which are assigned to the transitions of embedded impurity phases. The justification for this model is explained. Suggestions for future experimentation are also considered.